A Byzantine Logician’s “Image” within the Second Iconoclastic Controversy. Nikephoros of Constantinople - Goncharko, Oksana Yu. (Scrinium, 2017)
The article is devoted to the study of the single example of logical education in Byzantium – the famous two pages from the hagiography of Patriarch Nikephoros (†829) containing the list of chapter headings copied by Ignatios the Diacon from an elementary textbook of logic. It is argued that, during the disputes of the second iconoclastic controversy, Patriarch Nikephoros implemented almost all the elements of logical knowledge listed by Ignatios. The article represents a short overview connecting the standard logical topics from the 8th- and 9th-century education program with the variety of arguments and techniques used by Nikephoros in the Major Apology and the Antirrhetics. The authors try to reconstruct the “image” of Patriarch Nikephoros as a logician and to describe the logical educational standard of his epoch.